The Strategy of the Micro Business Assistance Program for the Snack Market Sektor Through Business Development Lectures in the Framework of Implementing Independent Learning on an Independent Campus (MBKM) - Suwarsi, Sri; Ayu Mahani, Septiana; Asro’i, Azib; Anasty Fahzaria, Nabilla; Rizqi, Muhammad; Rafi Addaar Quthni, Muhammad; Denisya, Bella (KnE Social Sciences, 2023)
Problems that can be identified are related to micro business activities in the snack market stall sector, namely the difficulty of marketing the products of market snacks sold in the stalls, because they only rely on traditional marketing and do not yet have an established brand; the absence of partners who act as mentors and collaborators in establishing a representative cake shop, and the lack of business capital or investment for the establishment of a cake shop for branding cakes for market snacks to upgrade. The study aims to initiate the establishment of a Pasar Snack Cake Shop in the city of Bandung as a branding strategy through clear stages by involving KBU-MBKM students under student business project in a real learning process, so as to achieve a link and match between the world business with the campus as an implementation of Merdeka Learning, Merdeka Campus. The solutions to the problems offered by the proposed activities are: i) providing direct tutorials to snack producers on product packaging, online marketing in collaboration with digital business partners such as Shopee export who have collaborated with the PKM Team in fostering MSMEs in West Java; ii) initiating the establishment of a representative cake shop in Bandung City by conducting a business feasibility study; iii) looking for investors for establishing a cake shop, so that its existence has long-term value. Keywords: mentoring, street food stalls, business development lectures (KBU), Merdeka Learning Merdeka Campus (MBKM)